118k views
2 votes
PLEASE HELP ME NOW I'M STUPID
simplify 3 ✔128 - 2✔6 x 4✔3

ALSO SHOW THE WORK PLEASE

User Ergonaut
by
6.0k points

2 Answers

3 votes


\bf 3√(128)-2√(6)* 4√(3)\implies 3√(128)-(2* 4)√(18)~~ \begin{cases} 128=2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\\ \qquad 2^6\cdot 2\\ \qquad 2^(3\cdot 2)\cdot 2\\ \qquad (2^3)^2\cdot 2\\ \qquad 8^2\cdot 2\\ 18=2\cdot 3\cdot 3\\ \qquad 2\cdot 3^2 \end{cases} \\\\\\ 3√(8^2\cdot 2)-8√(2\cdot 3^2)\implies 24√(2)-24√(2)\implies \boxed{0}

User Dimitris
by
5.4k points
5 votes

Answer: 0

Explanation:


3√(128) - (2√(6))(4√(3))

=
3√(128) - 2*4√(6*3)

=
3√(4*4*2*2*2) - 2*4√(2*3*3)

=
3*4*2√(2) - 2*4*3√(2)

=
24√(2) - 24√(2)

= 0

User Afrig Aminuddin
by
6.7k points